The immunological and social role of breastfeeding to prevent infectious and allergic diseases during childhood - Araújo, Márcio Flávio Moura de; Araújo, Thiago Moura de; Beserra, Eveline Pinheiro; Chaves, Emilia Soares (Rev Rene, 2006)
Reflexive study with the aim to analyze the immunological and social contribution of the mothers’ breastfeeding milk to prevent infectious and allergic diseases in children.The process of breastfeeding influences the children’s biopsychosocial development, especially, in the prevention of diseases such as diarrhea, IRAs and allergies that are associated to pediatric morbid-mortality causes. This immunity is obtained by the mothers’ antibodies, which are transmitted during breastfeeding. The main antibody in the milk is IgA that will reach the children’s digestive system preventing pathogenic microorganisms from multiplying in the children’s enterogastric system causing diseases. The nurses stood out in counseling the mothers and parturient women to assure breastfeeding carried on for six months. It must be pointed out that breastfeeding, due to its immunological and social characteristics that prevent many infectious and allergic diseases, consists in a health promotion action.